Dielectric studies of tetraethylene glycol-bis(3-methylimidazolium) dichloride (TEGDC) exhibiting large negative dielectric anisotropy - Yakuphanoğlu, Fahrettin; Okutan, M; Köysal, O; Özder, S; Ocakoglu, K; Içli, S (Amer Chemical Soc, 2005)
A dielectric anisotropy property of a TEGDC (tetraethylene glycol-bis(3-methylimidazolium) dichloride) is investigated as a function of frequency. TEGDC showed an extremely large negative dielectric anisotropy (-10.95 to -4753.73). Variation of dielectric anisotropy (Delta is an element of) with respect to the spot frequencies reveals that liquid crystal (LC) orientation has an n-type property at low frequencies and as the frequency increases dielectric anisotropy character shifts from negative dielectric anisotropy type (n-type) to positive dielectric anisotropy type (p-type). Consequently, the TEGDC is a liquid crystal with large negative dielectric anisotropy.
Keywords: Nematic Liquid-Crystals; Spectroscopy